The Influence of Administrative Anti-Monopoly Measures on the Innovation Enthusiasm of Digital Economy Enterprises and Countermeasures - Hou Jiayi (SHS Web of Conferences)
This paper deeply discusses the impact of administrative anti-monopoly measures on the innovation enthusiasm of digital economy enterprises, analyzes the characteristics of the rapid growth of the digital economy and platform economy, and discusses the challenges faced by administrative anti-monopoly in this industry. By interpreting the development status and innovation cases of domestic and foreign anti-monopoly laws and regulations, this paper reveals the positive role of digital economy administrative anti-monopoly regulation in promoting market fair competition, protecting consumers’ rights and interests, and encouraging enterprises’ innovation and points out the difficulties and existing problems of digital economy administrative anti-monopoly regulation, such as complicated market definition and lagging regulatory policies. Finally, countermeasures such as improving anti-monopoly laws and regulations, enhancing law enforcement and judicial capabilities, strengthening market definition and identification of monopoly behavior, and enhancing coordination and unification of administrative supervision are put forward, which provides policy suggestions for the healthy development of the digital economy.